2010
DOI: 10.1210/en.2010-0198
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Age and 17β-Estradiol on Kisspeptin, Neurokinin B, and Prodynorphin Gene Expression in the Arcuate-Median Eminence of Female Rhesus Macaques

Abstract: The neuropeptides kisspeptin, neurokinin B, and dynorphin A (collectively abbreviated as KNDy) are, respectively, encoded by KiSS-1, NKB, and PDYN and are coexpressed by neurons of the hypothalamic arcuate nucleus (ARC). Here, using quantitative real-time PCR, we examined agerelated changes in the expression of genes encoding KNDy and associated receptors G proteincoupled receptor 54 (encoded by GPR54), neurokinin 3 receptor (encoded by NK3), and -opioid receptor (encoded by KOR), in the female rhesus macaque … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
54
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(63 citation statements)
references
References 63 publications
7
54
0
2
Order By: Relevance
“…However, it has been shown in sheep that there are more than 40 fewer ARC Kiss1-positive neurons during the non-breeding season compared with the breeding season [28] and that the expression of Kiss1 in the ARC is markedly decreased by transition of sheep from short days (8L:16D) to long days (16L:8D) [29], whereas that from long days to short days increases the number of kisspeptin-positive neurons by approximately 50% [30]. Therefore, although we did not examine histology in ewes in the breeding season, it is plausible to think that the population of kisspeptin neurons observed in this study would be still considerably smaller than that during the breeding season.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it has been shown in sheep that there are more than 40 fewer ARC Kiss1-positive neurons during the non-breeding season compared with the breeding season [28] and that the expression of Kiss1 in the ARC is markedly decreased by transition of sheep from short days (8L:16D) to long days (16L:8D) [29], whereas that from long days to short days increases the number of kisspeptin-positive neurons by approximately 50% [30]. Therefore, although we did not examine histology in ewes in the breeding season, it is plausible to think that the population of kisspeptin neurons observed in this study would be still considerably smaller than that during the breeding season.…”
Section: Discussionmentioning
confidence: 99%
“…Because the decrease in the number of kisspeptin neurons during the non-breeding season is considered to be mainly due to the reduced expression of kisspeptin rather than to apoptosis [30], the very similar ratio of colocalization of kisspeptin and NKB between the breeding [13] and non-breeding seasons suggests that the expression of NKB in the ARC is also suppressed during the non-breeding season and that photoperiodic regulation of the expression occurs in a similar direction and extent between kisspeptin and NKB. In monkeys [30], rodents [9,31] and sheep [32], it has been shown that ovariectomy increases while E2 decreases the expression of NKB in the ARC, as is the case with kisspeptin [5,28]. Moreover, the number of kisspeptin- [33,34] and NKB-positive [34] neurons in the ARC are reduced in a similar manner during lactation in rats.…”
mentioning
confidence: 99%
“…Dynorphin signal was absent from most KP neurons and fibers, in contrast with the extensive coexpression reported previously in rodents [49,56,57,65], sheep [28,29,55] and goats [48]. Given that opioid peptides play important roles in the negative regulation of pulsatile prolactin and LH release in humans [66,67] and, similarly to the ARC of laboratory animals, the human Inf [68] and the monkey ARC [69] also express preprodynorphin mRNA, the absence of dynorphin immunoreactivity in the majority of KP-IR neurons of the human Inf (at least in young men) was somewhat unexpected [63]. Whether the negative colocalization data represent an important species difference in the human versus laboratory species or it is caused by postmortem degradation of dynorphin in KP-IR neuronal elements will require clarification.…”
Section: Major Groups Of Human Hypothalamic Kp Neuronsmentioning
confidence: 95%
“…In rodents, androgens as well as estrogens can upregulate KP expression in the RP3V [23,26,71] at the putative site of positive estrogen feedback [24]. In contrast, KP expression in the ARC/Inf is negatively regulated by sex steroid hormones in rodents and other mammals [23,26,69,71], as is NKB expression at this site [69,70,112]. Sex differences in the KP and NKB neuronal systems are partly caused by the activational effects of the gonadal steroid hormone milieu which changes depending on the reproductive status and differs in males and females.…”
Section: Sexual Dimorphism and Aging-dependent Changes In The Human Kmentioning
confidence: 99%
“…Many organs, including the brain, appear to express the enzymes necessary for this conversion, and it is well established that sex steroids can exert neuroprotective effects in brain areas such as the hippocampus [53]. Because estrogen can improve cognitive function and influence gene expression in various regions of the macaque brain [54,55,56,57,58], it is plausible that DHEA and DHEAS mediate some of their central actions via conversion to estrogen. It is also plausible that the age-related loss of humoral circadian signaling due to attenuated DHEA and DHEAS levels contributes to age-related desynchronization of peripheral oscillators and exacerbation of circadian dissonance in the elderly.…”
Section: Circadian Hormone Rhythms Help With Adaptation To Daily Envimentioning
confidence: 99%